EThNIC TOLERANCE FORMATION OF STUDENTS ON ThE PRINCIPLES OF MULTICULTURALISM - Xiaoxing, Zhang (The Modern Higher Education Review, 2016)
The paper presents a theoretical and methodological substantiation processes connections of multicultural education and the formation of ethnic tolerance of students. Historical and pedagogical analysis of the formation of positive emotional and value attitude to people of other nationalities have been done. The principle of multiculturalism is defined as a pedagogical standard of human involvement to an ethnic, national and world cultures, forming readiness to live in a multiethnic environment. In the article the role of tolerance of the individual regulation of relations in today’s multicultural society is highlighted. Social transformation processes are characterized which actualize search methods of formation of ethnic tolerance in a multicultural area of the country. Ethnic tolerance is described as psychosocial quality of the individual that is ready for cooperation, partnership, cultural interchange, which is based on the principles of mutual understanding and patience. Pedagogical conditions and principles of ethnic tolerance of students on the basis of multiculturalism in social and educational activities of the university.